Maintaining Integrity The Importance of Professional Ethics in the World of Work - Amiruddin; Pratama, Chandra Wisnu Aji; Aldiva Hamzah Hasibuan; Wisda Anggriyani (Bahasa Indonesia, 2024)
This article explores the importance of professional ethics in the context of the modern world of work. The aim of the research is to investigate the awareness and understanding of professional ethics among professionals and to evaluate its influence on individual performance and the organizational work environment. The research method used is a qualitative approach with a phenomenological design, involving in-depth interviews, participant observation and document analysis. The research ethics results show that awareness of professional influences decision making and daily behavior in the workplace, while consistent application of professional ethics contributes to improving performance and strengthening the company's reputation. Challenges faced include pressure to achieve business targets, lack of management support, and a competitive external environment. In conclusion, professional ethics are not only important for maintaining individual integrity, but also play a crucial role in creating a productive and ethical work environment and building a strong reputation for the organization.